Image of the Hero Alisher Navoyi in Oibek's Novel "Navoi" (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article examines the image of Alisher Navoi in Oybek’s novel “Navoi”. In a historical novel, the author puts forward the concept of a historical person in the image of the main character's writer. Oybek’s work is a historical-biographical novel not only because in it data about Navoi’s personality sets in motion the plot, composition and conflict of the work. This is also due to the presence of important information and facts relating to such historical figures as Hussein Baykara, Majiddin, Badiuzzaman, Muzaffar Mirzo, Khadicha Begim, Binai, Jami, Mumin Mirzo, and others.